Alcohol consumption and risk of recurrent cardiovascular events and mortality in patients with clinically manifest vascular disease and diabetes mellitus: The Second Manifestations of ARTerial (SMART) disease study - Beulens, J.W.J.; Algra, A.; Soedamah-Muthu, S.S.; Visseren, F.L.J.; Grobbee, D.E.; van der Graaf, Y. (Atherosclerosis, 2010)
This study investigated the relation between alcohol consumption and specific vascular events and mortality in a high risk population of patients with clinical manifestations of vascular disease and diabetes. Patients with clinically manifest vascular disease or diabetes (n=5447) from the SMART study were followed for cardiovascular events and mortality. Alcohol consumption was assessed with a baseline questionnaire and analysed in relation with coronary heart disease (CHD), amputations, stroke, and all-cause and vascular death. After a follow up of 4.7 years, we documented 363 cases of CHD, 187 cases of stroke, 79 amputations and 641 cases of all-cause death, of which 382 were vascular. In multivariate-adjusted models, alcohol consumption was inversely associated with CHD (plinear trend=0.007) and stroke (plinear trend=0.051) with respective hazard ratios of 0.39 (95%CI: 0.20–0.76) and 0.67 (0.31–1.46) for consuming 10–20 drinks/week compared with abstainers. We observed significant U-shaped associations between alcohol consumption and amputations (pquadratic trend=0.001), all-cause death (pquadratic trend=0.001) and vascular death (pquadratic trend=0.013). Hazard ratios for consuming 10–20 drinks/week were 0.29 (0.07–1.30) for amputations, 0.40 (0.24–0.69) for all-cause death and 0.34 (0.16–0.71) for vascular death compared with abstainers. Similar associations were observed for red wine consumption only. Moderate alcohol consumption (1–2 drinks/day) is not only associated with a reduced risk of vascular and all-cause death in a high risk patients with clinical manifestations of vascular disease, but also with reduced risks of non-fatal events like CHD, stroke and possibly amputations.